Sated by a Zero-Calorie Sweetener: Wastewater Bacteria Can Feed on Acesulfame - Kleinsteuber, Sabine; Rohwerder, Thore; Lohse, Ute; Seiwert, Bettina; Reemtsma, Thorsten (Frontiers in Microbiology, 2019)
The widely used artificial sweetener acesulfame K has long been considered recalcitrant in biological wastewater treatment. Due to its persistence and mobility in the aquatic environment, acesulfame has been used as marker substance for wastewater input in surface water and groundwater. However, recent studies indicated that the potential to remove this xenobiotic compound is emerging in wastewater treatment plants worldwide, leading to decreasing mass loads in receiving waters despite unchanged human consumption patterns. Here we show evidence that acesulfame can be mineralized in a catabolic process and used as sole carbon source by bacterial pure strains isolated from activated sludge and identified as Bosea sp. and Chelatococcus sp. The strains mineralize 1 g/L acesulfame K within 8-9 days. We discuss the potential degradation pathway and how this novel catabolic trait confirms the ‘principle of microbial infallibility’. Once the enzymes involved in acesulfame degradation and their genes are identified, it will be possible to survey diverse environments and trace back the evolutionary origin as well as the mechanisms of global distribution and establishment of such a new catabolic trait.